Composition of cardiac troponin release differs after marathon running and myocardial infarction - Olli J Heinonen; K E Juhani Airaksinen; Konsta Teppo; Tuomas Paana; Tuija Vasankari; Selma Salonen; Tuulia Tuominen; Anna Linko-Parvinen; Hanna-Mari Pallari; Tapio Hellman; Samuli Jaakkola; Saara Wittfooth (Open Heart, 2024)
Objectives Elevations of cardiac troponin T (cTnT) levels are common after strenuous exercise. We assessed whether the composition of cTnT release after marathon race differs from that of acute myocardial infarction (MI).Methods Troponin composition was analysed in plasma samples taken from 45 runners after marathon race and from 84 patients with type 1 MI. The concentration of long cTnT (intact and mildly fragmented cTnT) was measured with a novel upconversion luminescence immunoassay, total cTnT with a commercial high-sensitivity cTnT assay, and the ratio of long to total cTnT (troponin ratio) was determined as a measure of troponin fragmentation.Results Total cTnT exceeded the upper reference limit (>14 ng/L) in 37 (82%) runners. Troponin ratio was lower in runners ((IQR) 0.17 (0.11–0.24) vs 0.62 (0.29–0.96), p<0.001). With increasing troponin release the troponin ratio decreased (r=−0.497, p<0.001) in marathon runners and the concentration of long cTnT remained in all runners below 8.4 ng/L. In contrast to marathon runners, troponin ratio increased (r=0.565, p<0.001) with the increase of cTnT release in patients with MI. The median total and long cTnT concentrations were lower in marathon runners than in patients with MI (25 ng/L vs 835 ng/L and 4.1 vs 385 ng/L, p<0.001 for both).Conclusion In contrast to type 1 MI, only a small fraction of circulating cTnT exists as intact cTnT or long molecular forms after strenuous exercise and the difference in troponin composition is more pronounced in runners with higher troponin release.Trial registration number NCT06000930.